Membangun Kesadaran Masyarakat Dalam Menjaga Kebersihan Lingkungan Serta Sosialisasi Pencegahan dan Penanggulangan Virus Dengue Kepada Masyarakat di Lingkungan RW 07 - Kariswandana, Raihan Lutfan; Baihaqi, Fahri; Wijaya, Andika Risky; Novianto, Danang; Endika, Rafid; Aulia, Ario Wildan; Putra, Anak Agung Ngurah Angga; Wijaya, Hadi Candra; Safar, Muhamad Difari; Sandy, Rafly Septia; Naidir, Ferra (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
The collaboration by the University of Bhayangkara Jakarta Raya and RW 07 Marga Mulya Village aims to increase public awareness of the cleanliness and beauty of the surrounding environment. In addition, the purpose of the collaboration is to increase public knowledge of various diseases, especially Dengue Fever. In this community service KKN activity, it is proposed that facilities be procured, and a movement to improve the environment, socialize knowledge, and prevent DHF is proposed. The object of service is the entire community of RW 07 Marga Mulya Village. This activity focuses on developing facilities and building a clean and disease-free environment. There are 4 Activity Programs consisting of the fields of K3 and Health. Our KKN activity program is expected to be a model for similar programs in the future to improve health and environmental sustainability. This activity was responded to well by the leaders and the community with good communication so that we could run the activity program according to the objectives.